The political impossibility of modern counterinsurgency: strategic problems, puzzles, and paradoxes - Smith, M. L. R. (Columbia studies in terrorism and irregular warfare, 2015)
1. What is Counterinsurgency Meant to Counter? The Puzzle of Insurgency 1. - 2. Counterinsurgency and Strategy: Problems and Paradoxes 29. - 3. Counterinsurgency and the Ideology of Modernization 55. - 4. The Paradoxes of Counterinsurgency and Globalization 89. - 5. The Illusion of Tradition: Myths and Paradoxes of British Counterinsurgency 119. - 6. The Puzzle of Counterinsurgency and Escalation 151. - Conclusion 179